OPTIMUM DESIGN OF ASPHALT CONCRETE MIXES BASED ON ANALYTICAL APPROACH - Purwadi, Dikdik
OPTIMUM DESIGN OF ASPHALT CONCRETE MIXES BASED ON ANALYTICAL APPROACH, Didik Purwadi, 1995, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. Asphalt concrete is originally from The United States and has become the most popular highway surface in Indonesia, because it is suitable for highways carrying heavy traffic. As a result of the national development programme there has been a rapid growth in road transport in recent years. Since the forties there has been a sustained interest in the development of fundamental structural procedures. These attempt to relate the stresses and strains caused by traffic on pavement materials with the performance of those materials under repetitive loading. This is also known as the analytical procedure. However, the methods of pavement design which have evolved world-wide since the second world war have largely been derived empirically from the results of full-scale experiments, and the detailed study of the performance of in-service roads. In 1983, based on analytical analysis, the Asphalt Institute built the computer program DAMA. The objective of the study was to know the optimum bitumen content of the surfacing layer and its relation to the surface thickness. The four surface layer thicknesses which were adopted, 100, 200, 300 and 400mm, and by the analytical calculation with 75 blows of compaction and 200mm surface layer thickness gave the optimum bitumen content result of 4.71%. The optimum bitumen contents of the material were 6.58, 6.37, 5.43 and 5.90% for 35,50,75 and 100 compaction blows respectively. The two optimum bitumen contents were taken to be compared. The one from the analytical procedure of the DAMA program was 4.71%. The other, from empirical analysis of 75 blows of compaction, was of 5.43%. The optimum bitumen content resulted from the analytical approach by using the DAMA program was lower than the optimum bitumen content resulted from empirical analysis (Marshall test). Surface layer thickness governs a significant factor in a pavements life. Two pavements can have the same life even if they are different thicknesses because of the different levels of compaction, bitumen content and volume of voids